Providing RC5 Security for Messages in Android Based Mobile Devices for Achieving Confidentiality - Khan, Shahebaz Ahmed; Padmanabham, P; Naganjaneyulu, KV (International Journal of Computer Sciences and Engineering, 2025)
The idea of this paper is to study the symmetric key algorithms like DES, RC5, AES, Triple DES, BLOWFISH etc. so that the better algorithm can be picked to import its functionality in the Android based mobile devices. Here, we analyse their performance mainly this beats, end memory requirements and speed are studied to pick suitable algorithms to be implemented on the mobile and handheld devices. The above algorithms will be first implemented in C, C++ or JAVA and their performance will be analysed. The proposal extends as when an encrypted message is sent from one mobile phone to the other, a standard and essential key is provided which is symmetric in nature. If any of the two or more parties want to open the message that is sent to them, they have to utilize the secret code in the provided key without leaving a single digit. The message will be decrypted only after the full key version is matched with the given symmetry of the key .This makes the data or any information more secure even in the mobile devices for the common users by non-repudiation. This ensures the use of cryptography and its advantages by the end users of mobile phones for confidentiality.